Ivermectin Plasma Concentration in Iberian Ibex (Capra pyrenaica) Following Oral Administration: A Pilot Study - Moroni, Barbara; Granados Torres, José Enrique; López-Olvera, Jorge Ramón; Espinosa Cerrato, José; Ráez Bravo, Arián; Mentaberre, Gregorio; Fandos, Paulino; Pazzi, Marco; Romagnoli, Monica; Gardini, Giulia; Rossi, Luca; Valldeperes, Marta; et al. (Frontiers in veterinary science, 2022)
Sarcoptic mange is considered the main driver of demographic declines occurred in the last decades in Iberian ibex ( Capra pyrenaica ) populations. Mass treatment campaigns by administration of in-feed acaricides are used as a measure to mitigate the impact of mange in the affected populations. However, there are no data on ivermectin (IVM) pharmacokinetics in this wild caprine, and the treatment through medicated feed is not endorsed by evidence on its effectiveness. The aim of this study is to determine the pharmacokinetic profile of IVM in plasma samples of ibexes after the experimental oral administration of IVM, using high performance liquid chromatography (HPLC) with automated solid phase extraction and fluorescence detection. A dose of 500 μg of IVM per body weight was orally administered in a feed bolus to nine healthy adult ibexes (seven males and two females). Blood samples were collected by jugular venipuncture into heparin-coated tubes at day 1, 2, 3, 4, 7, 10, 15, and 45 post-administration (dpa). The highest plasma concentration of IVM (Cmax = 3.4 ng/ml) was detected 24 h after the oral administration (T1), followed by a rapid decrease during the first week post-administration. Our results reveal that plasma IVM concentration drops drastically within 5 days of ingestion, questioning the effectiveness of a single in-feed dose of this drug to control sarcoptic mange. To the best of our knowledge, this is the first study on plasma availability of oral IVM in ibexes and in any wild ungulate species.